Robots and Communication - Sandry, E. author. aut Link
XII, 129 p.
Keywords: This book explores communication between humans and robots. Using a range of communication theories, it highlights how each theory provides a different perspective on the communication that occurs. The analysis of human interactions with a variety of forms of robot suggests new ways to perceive what communication, and being a communicator, entails.